Prevalence of ideation and attempted suicide among users of a psychosocial care center - Luciane Prado Kantorski; Ariane da Cruz Guedes; Camila Irigonhé Ramos; Carlos Alberto dos Santos Treichel; Dariane Lima Portela; Janaína Quinzen Willrich; Vanda Maria da Rosa Jardim; Vinícius Boldt dos Santos (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective This study aims at identifying and characterizing the prevalence of suicidal ideation and attempted suicide among users of a Psychosocial Care Center in the municipality of Pelotas (RS). Method Transversal study, documentary based study in 389 active medical records. Data collection were carried out between September 2017 and May 2018. Data were digitated in the software Microsoft Excel and afterwards converted for the statistical Stata 11 Software. Results The prevalence of ideation and attempted suicide was 48,1% and 33,4%, respectively. Significant differences were observed in relation to hearing voices (p=<0,001) and history of violence (p=<0,001). Users who heard voices presented prevalence of suicidal ideation corresponding to 58,1%. Among those users who have reported suicidal ideation, the prevalence of attempt was 57,7%, while the users without report of ideation, the attempts were prevalent in 10,9% (p=<0.001). Conclusions The users presented a significant prevalence of ideation and attempted suicide.